Tin(IV) Halides Zero-dimensional based Inorganic-Organic Hybrid Materials: Crystal Structures and Hirshfeld Surface Analysis - Ndiaye, Mamadou; Pouye, Serigne Fallou; Diop, Mouhamadou Birame; Diop, Libasse; Samb, Abdoulaye; Oliver, Allen G. (Earthline Journal of Chemical Sciences, 2023)
Two tetramethylguanidinium halostannate inorganic-organic hybrid compounds was isolated and structurally investigated by single crystal X-ray crystallography and Hirshfeld surface analysis. The compound [(C6H14N3)2SnCl6] (1), crystallizes in the orthorhombic space group Fddd with Z = 8 / Z’ = 0.25, a = 7.3474(3) Å, b = 22.3678(8) Å, c = 28.4908(10) Å and V = 4682.3(3) Å3. The compound [(C6H14N3)2SnBr6] (2), crystallizes in the orthorhombic space group Fddd with Z = 8 / Z’ = 0.25, a = 7.5767(5) Å, b = 23.0591(17) Å, c = 29.008(2) Å and V = 5068.0(6) Å3. The isolation of 1 undergoes a redox process from Sn(II) to Sn(IV) in solution and in a non-controlled atmosphere. Both compounds 1 and 2 describe TMG+ ions with a central carbon atom in a trigonal–planar fashion. With respect to this CN3 plane, the pairs of dimethylammonium groups are twisted by 13.70 (8) and 32.21 (8)° for 1, 14.88 (13) and 31.95(13)° for 2. The SnX6 dianions evidence a slightly distorted octahedron (Oh) about Sn centre for hybrids 1 and 2. Within the structures of the hybrid materials 1 and 2, N-H···Cl inter-species hydrogen bonding patterns between the inorganic stannate and the organic entities give rise a one-dimensional chain, wherein inorganic and organic species alternate. The propagation of the chain generates rings. The weak C-H···X hydrogen bonds formed from the methyl groups to adjacent tetramethylguanidinium-stannate chains result in a supramolecular three-dimensional hydrogen-bonded network. The Hirshfeld surface analysis shows existence of both strong and weak hydrogen bonding interactions. Inspection of 1 and 2 by the Hirshfeld surface analysis, show isostructural behavior. Hybrids 1 and 2 are the first crystal reports of a tetramethylguanidinium tetra- or hexa-halostannate.